3D non‐stationary geometry‐based multi‐input multi‐output channel model for UAV‐ground communication systems. Issue 8 (5th June 2019) - Zhu, Qiuming; Wang, Yawen; Jiang, Kaili; Chen, Xiaomin; Zhong, Weizhi; Ahmed, Naeem
Abstract : Unmanned aerial vehicles (UAVs) with multi‐input–multi‐output technologies are considered as a promising platform to provide future high‐speed wireless communication services. In this study, considering three‐dimensional (3D) antenna arrays and 3D arbitrary trajectories of the UAV and mobile terminal, the authors propose a new 3D non‐stationary geometry‐based stochastic channel model for UAV‐ground communication systems. Under 3D non‐isotropic scattering scenarios, the computation and optimisation methods of time‐variant channel parameters are investigated. In addition, the theoretical statistical properties such as the autocorrelation function, cross‐correlation function, Doppler power spectrum density, level‐crossing rate, and average fading duration are analysed and derived. Finally, the usefulness of the proposed model as well as theoretical derivations are verified by the comparison between theoretical, simulated, and measured results.